Characterization of the Vascular Bundles in Thyrsostachys oliveri - Haoxiang Fang; Linpeng Yu; Yuxuan Chen; Xianghua Yue; Bin Xu; Genlin Tian (BioResources)
The characteristics of vascular bundles vary significantly across different heights in bamboo. Thus, a comprehensive understanding of vascular bundles is crucial for the identification and efficient utilization of bamboo materials. In this work, the structure and type of vascular bundles in Thyrsostachys oliveri at different heights were investigated. The results revealed substantial differences in the types of vascular bundles in T. oliveri at various heights within the bamboo. The radial diameter exhibited no significant differences in the radial variation of fiber sheath area at different heights, whereas the tangential diameter showed differences in the radial variation between the upper and lower middle parts of the bamboo. This study provides insights into the structural variations of vascular bundles in T. oliveri at different heights, which are beneficial for optimizing the use of bamboo materials in various applications.